PERANCANGAN BUKU ILUSTRASI TENTANG PENTINGNYA PENAMPILAN DIRI BAGI REMAJA USIA 11-17 TAHUN - Natalie, Yenni; Nirwana, Aditya; Sukmaraga, Ayyub Anshari (Sainsbertek Jurnal Ilmiah Sains & Teknologi, 2025)
Appearance is something we must pay attention to. Having a good, neat and appropriate appearance will form a good first impression. Appearance is not only seen from the clothes worn, but also the cleanliness and health of the body. Various aspects that need to be considered to maximize appearance are maintaining and caring for the body and face. To introduce the importance of paying attention for appearance to teenagers, by providing media that can be an inspiration for teenagers to pay attention to their appearance, author designed the ilustration book. Books are an easy medium to convey knowledge, entertainment and various other message contents. This illustrated educational book will present various tips for managing a good lifestyle.